ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN BERBASIS DARING PADA SISWA SEKOLAH DASAR - Rahmi Gunarwati; Luthfi Hamdani Maula; Iis Nurasiah (JANACITTA, 2021)
This research is motivated by the low reading comprehension ablility of sudents. This study aims to find out how the online-based learning process for reading comprension skills is and how the online-based assesment process for reading comprehension skills is. As for this type of researsh using descriptive method. Data were collected by means of in-depth interviews and daocumentation. The subjects in this study were the fifth grade elementary scools students, totaling 30 students. Based on the description of the data obtained from discussion of the results of the research that has been carried out, it can be conckuded that the online-based reading comprehension ability of SDB Tunas Harapan students is in the suffictient category, altthogh there are some who are lacking in reading comprension ablility. The results of the reading comprehension test of students who met the KKM were 23 people, while for students who did not meet the KKM were 7 people, with an average score of 71,2. From the result of this study, the online based reading comprehension ability of SDN Tunas Harapan Students is in theÂ  suffiction category, for the highest score of students on this test is 90 while the lowest score is 25. Students who have not met the KKM are due to lack of cognitive ability, and do not concentrate when reading or reading. Do not understand the material that has been delivered by the teacher so that the ability of student to answer the question becomes difficult. Support from the teacher or the people around him in reading must always be there and done so that students feel motivated and interest in readinf better in order to add knowlodge and broad insight.Â Keyword: Reading Comprehension Ability, Online Learning